New low-mass members of the Octans stellar association and an updated 30-40 Myr lithium age - Murphy, Simon J.; Lawson, Warrick (Monthly notices of the Royal Astronomical Society, 2015)
Abstract. The Octans association is one of several young stellar moving groups recently discovered in the Solar neighbourhood and hence a valuable laboratory